Pengembangan Video Pembelajaran Berbasis Capcut dalam Menulis Teks Pidato Siswa Kelas VIII UPTD SMP Negeri 2 Gunungsitoli Utara - Zega, Boy Damai Putra; Halawa, Noibe; Waruwu, Lestari; Zega, Imansudi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop Capcut-Based Learning Videos on Writing Texts for Speech for VIII Grade Students of UPTD SMP Negeri 2 Gunungsitoli Utara. The method used in this study is research and development (Research & Development). The developed learning videos use the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicate that the developed learning videos have undergone a validation process by three experts, namely a content expert, language expert, and design expert. The validation results show that the content expert rated it 96%, the language expert rated it 94%, and the design expert rated it 82%. This percentage indicates that the Capcut-based learning videos developed meet the feasibility criteria in terms of content, language, and design appearance. The practicality of the learning media was tested through three stages, namely individual trials (89%), small group trials (88%), and field trials (90%). These results indicate that the media is easy to use both individually and in real learning situations. The effectiveness of the learning media is measured by the students' learning completeness after using Capcut-based videos. The results show a completeness of 100% in individual trials, 83% in small groups, and 94% in field trials. Thus, the development of Capcut-based learning videos has been proven valid, practical, and effective for use in the learning process